2010
DOI: 10.4012/dmj.2009-016
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Candida albicans formation on feldspathic porcelain subjected to four surface treatment methods

Abstract: Candida albicans, known for its adhesion on prosthetic materials and oral tissues, is the most frequently encountered fungal infection in dentistry. The aim of this study was to evaluate the effects of four different surface treatment methods and immersion in artificial saliva on the surface roughness of and candida adhesion on dental porcelains. The four surface treatment methods were namely: natural glaze, overglaze, dual ion exchange, and polishing. Surface roughness of porcelain was evaluated using a surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 21 publications
0
11
0
1
Order By: Relevance
“…Furthermore, the glazing process reduces porosity on the surface of the ceramic material 9,47 and the lower the roughness on such surfaces, the lower the risk of micro-organism colonization, e.g., Candida albicans from the intraoral environment. 45 Brushing, on the other hand, did not alter hardness on the glazed feldspathic ceramic, perhaps due to its abrasive effect, which could consequently reflect on surface roughness. Regarding surface roughness, the null hypothesis was also rejected because prefabricated trays loaded with hydrogen peroxide at a concentration of 10% were able to induce the highest average roughness values on the glazed feldspathic ceramic surface, independent from brushing cycles.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Furthermore, the glazing process reduces porosity on the surface of the ceramic material 9,47 and the lower the roughness on such surfaces, the lower the risk of micro-organism colonization, e.g., Candida albicans from the intraoral environment. 45 Brushing, on the other hand, did not alter hardness on the glazed feldspathic ceramic, perhaps due to its abrasive effect, which could consequently reflect on surface roughness. Regarding surface roughness, the null hypothesis was also rejected because prefabricated trays loaded with hydrogen peroxide at a concentration of 10% were able to induce the highest average roughness values on the glazed feldspathic ceramic surface, independent from brushing cycles.…”
Section: Discussionmentioning
confidence: 85%
“…The specimens were glazed to simulate a clinical scenario. Furthermore, the glazing process reduces porosity on the surface of the ceramic material and the lower the roughness on such surfaces, the lower the risk of micro‐organism colonization, e.g., Candida albicans from the intraoral environment . Brushing, on the other hand, did not alter hardness on the glazed feldspathic ceramic, perhaps due to its abrasive effect, which could consequently reflect on surface roughness.…”
Section: Discussionmentioning
confidence: 97%
“…20 Surface profilometry is suitable for quantitative assessment of surface roughness. 21 However, in some cases, the roughness values do not truly represent the actual topography of ceramic surfaces because only some areas, and not the whole surface, are probed by the profilometer. 22 Therefore, SEM has also been recommended to obtain more comprehensive results 22 since SEM provides high-resolution information regarding surface texture details and enhances qualitative assessment of surface topography.…”
mentioning
confidence: 99%
“…In addition, surface deterioration will facilitate the involvement of plaque and microorganisms (Honorio et al 2008). Karayazgan et al (2010) reported that the level of adhesion of Candida albicans to the polished surface of feldspathic porcelain was 3.4 ± 0.25 colonies/mm 2 . In a similar study, enamel used as the control for assessment of the adhesion of Streptococcus mutans to uncoated and saliva-coated glass ceramics and composites (Kantorski et al 2008) and their report was consistent with the fi ndings of the current study.…”
Section: Resultsmentioning
confidence: 99%